Experiences and factors that influence potassium hydroxide examination by microscopists - Sumanas Bunyaratavej (2018)
© 2016, Japanese Society for Medical Mycology. All rights reserved. Background: Potassium hydroxide (KOH) examination is commonly used in dermatological practice. Despite its simplicity, rapidity, and minimal invasiveness, experience in specimen collection, preparation, and interpretation is extremely important. Aims: To determine the ability to interpret KOH examination of six microscopists with different levels of experience within the Department of Dermatology. Methods: Six volunteer microscopists, who have different experiences in KOH examination in terms of specimens per week (SPW), were assigned to prepare and examine 10 unknown slides of skin scrapings. All participants were then paired into three groups and exchanged the slides set to their partner in each group for a second round of slides interpretation. Results: Results of examinations were classified as correct, false negative, false positive, and misinterpretation. The highly experienced microscopists achieved more correct answers than the fairly experienced group in both sessions. There was a significant positive correlation between SPW (r = 1.0, Spearman rank, p = 0.01) and the correct answers; and a significant negative correlation between SPW and misinterpretation(r = -1.0, Spearman rank, p < 0.01), exclusively for the second session. Limitations: A small number of volunteer microscopists was enrolled in this study. Conclusions: Experience in routine slide examination and time spent during examination were significant factors for accurate interpretation of KOH examination. Positive correlation between experience and correct answers, and negative correlation between experience and misinterpretation were particularly observed under limited examination time.